Implementation of complex engineering problems (CEP) and complex engineering activities (CEA) of undergraduate programmes in Malaysia - Mohamed Azmin, Nor Fadhillah; Mat Isa, Che Maznah; Oh, Chai Lian; Asnawi, Ani Liza (Global Academic Excellence (GAE), 2025)
For decades, complex problem-solving skill has been identified as one of the key components required from fresh graduates to succeed in the workforce market. Specific for engineering undergraduate programmes in Malaysia, the Engineering Accreditation Council (EAC) Standard 2020 has prescribed the complex engineering problem (CEP) solving skills and complex engineering activities (CEA) as a part of its graduate attributes. However, in many cases, engineering programmes lack of a clear understanding of the requirements of complex engineering problems, hindering the students' mastery of engineering related problem-solving skills to face real-world problems’ complexity. In this paper, an evaluation on the awareness and implementation of complex problem solving (CEP) skills and complex engineering activities (CEA) in the undergraduate engineering programmes in Malaysia is presented. Survey questionnaires were designed to gather feedback from academicians across various higher learning institutions (HLIs) that offer engineering programmes. This study which involves 120 experienced engineering lecturers from 23 public and private HLIs shows that project-based courses is the common courses chosen to address CEP and CEA including final year project, integrated design project, and design-related courses. The assessments of CEP and CEA are mostly conducted on a semester basis, utilizing project-based assessment. Problem-based learning (PBL) is the most widely chosen as teaching and learning strategy, engaging students in solving real-world problems, encouraging active participation, critical thinking, and the application of knowledge. In summary, this study contributes to understanding how CEP and CEA are implemented in undergraduate engineering programmes, and thereby represents a general framework to aid with the implementation of CEP and CEA in engineering education. Further research could explore the effectiveness and impact of these teaching and learning strategies on students' learning outcomes, students’ abilities to apply CEP and CEA principles in real-world scenarios